Probabilistic analysis of solar photovoltaic output based on historical data - Zulkifli N.A.; Razali N.M.M.; Marsadek M.; Ramasamy A.K. (IEEE Computer Society, 2023)
Solar photovoltaic (PV) is one of the favorable renewable energy sources since it is considered environmentally friendly. Yet it is still at the infancy stage due to the high cost of PV cells. Furthermore, the PV output is dependent on the solar radiation intermittency and the location of installation. This paper presents a probabilistic analysis of a hypothetical solar photovoltaic system in Peninsular Malaysia. From the recorded meteorological data, an analysis of the probabilistic distribution function of the hourly solar radiation is carried out. A comparison has been made between two different locations in order to analyse their characteristics by using meteorological data of KLIA Sepang and Kuala Terengganu Airport. This paper adopts a method considering a multi-state model instead of two-state model which is used for modeling conventional generator to cater for the intermittency of solar radiation. A linear rounding method is recommended for simplification of the multi-state model for effective computation. The results show that based on irradiance data in Peninsular Malaysia, development of microgrid containing solar photovoltaic power system has a good potential for further development. © 2014 IEEE.